The Effect of Hermetia illucens Larvae on the Hematology of Tilapia (Oreochromis niloticus) Infected Edwardsiella tarda - Tirani, Elisabeth; Maftuch, Maftuch; Fadjar, Mohammad; Awaluddin, Muhammad (Journal of Aquaculture and Fish Health, 2024)
Non-specific defense is the main defense in fish. One of the natural ingredients as a source immunostimulant is H. illucens larvae with a protein content of up to 30%. H. illucens larvae contains alkaloids, tannins, terpenoids and saponins as immunostimulating agents. Immunostimulants are biological compounds that can boost the immune system body. The purpose of this study is to find out the effect of H. illucens larvae in increasing immunity non specific in tilapia (O. niloticus) which infected with E. tarda. In giving H. illucens larvae feed ad libitum with concentrations of A(30%), B(40%), C(50%), K(0%). In this research method, a completely randomized design (CRD) was used with 5 treatments and 3 replications in which each aquarium contained 10 tilapia. Parameters tested are leukocytes, differential leukocytes, erythrocytes and hemoglobin. The results showed that intake of 50% H. illucens larvae on tilapia could increase non-specific immunity, such as total leukocytes, total erythrocytes, differential leukocytes, hemoglobin